Desenvolvimento e validação de método por cromatografia gasosa acoplada a espectrometria de massas sequencial para análise de resíduos de anabolizantes em urina de bovinos - Amanda Lemes Silveira (2017)
This work involved the optimization and validation of a method of identification and quantification of anabolic residues in bovine urine by gas chromatography tandem mass spectrometry.The enzymatic hydrolysis optimization indicated the best condition at 37.5°C for 16 hours, using a -glucuronidase sulfatase enzyme of Helix pomatia at pH 5.2. The extraction and purification optimization consisted of liquid-liquid extraction with diethyl ether and solid phase extraction with HLB and aminopropylsilane cartridges. A derivatization with MSTFA/NH4I/ethanethiol was optimized through the 33 Box-Behnken factorial desing, evaluating the factors: time, microwave power and volume of derivatization reagent. The optimal condition consisted of reaction for 2 minutes with 25 L of derivatizing and power of 900 W. Another derivatization procedure was performed for 17-trenbolone and 17-trenbolone, using MSTFA/I2 followed by pure MSTFA. The validation parameters evaluated were: linearity range, selectivity, precision, veracity, decision limit, detection capability, limit of detection, limit of quantification, and uncertainty. The analytical curves, for all the analytes, were adjusted to the linear fit. The method was selective for the analytes under study, against the interfering avermectins. The accuracy of the method was considered adequate (90.5-132.4%) for the analyzed analytes, with the exception of -estradiol, zeranol, -zearalenol and norethandrolone. Repeatability (2.9-43.0%) and intermediate precision (3.6-36.4%) were considered adequate for all analytes. The decision limit values (0.03-0.99 g kg-1), detection capacity (0.05-1.68 g kg-1) and measurement uncertainty (0.130-1.487 g kg-1) were considered adequate for all analytes. In the limit of quantification values the method presented satisfactory accuracy (5.6-49.5%) for all analytes, and recovery (58.8-138.8%) was also considered adequate, except for zearalenone, -zearalenol, -zearalenol, -trenbolone and -trenbolone. Analyzes of real bovine urine samples were performed and the results obtained corroborated with the results obtained by liquid chromatography tandem mass spectrometry.